Transitioning out of the professional player pathway: A grounded theory on the process in South African Men’s tennis - Skinstad, Deborah Anne; Stellenbosch University. Faculty of Medical and Health Sciences. Dept. of Sport Science. (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD Sport Sc)--Stellenbosch University, 2022.